Retropharyngeal Hematoma Secondary to Minor Blunt Trauma Neck: A Rare Case Report - Dipten Paul; Shubhrakanti Sen; Avishek Palai; Monoj Mukherjee (Bengal Journal of Otolaryngology and Head Neck Surgery, 2015)
Introduction